2018
DOI: 10.3389/fnins.2018.00744
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Atrophy Is Associated With Cognitive Impairment in Patients With Presbycusis: A Comprehensive Morphometric Study

Abstract: Presbycusis (PC) is characterized by bilateral sensorineural hearing loss at high frequencies and speech-perception difficulties in noisy environments and has a strikingly detrimental impact on cognitive function. As the neural consequences of PC may involve the whole brain, we hypothesized that patients with PC would show structural alterations not only in the auditory cortex but also in the cortexes involved in cognitive function. The purpose of this study was to use surface-based morphometry (SBM) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 42 publications
11
51
0
Order By: Relevance
“…Previous studies have related audiogram threshold loss with right temporal and cingulate cortex atrophy [9-12,40,41]. Here we extended these results, showing that in addition to audiogram threshold elevation, reduced suprathreshold amplitudes of auditory nerve responses are associated to a reduction of the thickness of bilateral middle and inferior temporal cortices, and right posterior cingulate cortex.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have related audiogram threshold loss with right temporal and cingulate cortex atrophy [9-12,40,41]. Here we extended these results, showing that in addition to audiogram threshold elevation, reduced suprathreshold amplitudes of auditory nerve responses are associated to a reduction of the thickness of bilateral middle and inferior temporal cortices, and right posterior cingulate cortex.…”
Section: Discussionsupporting
confidence: 81%
“…Presbycusis is also associated with executive dysfunction [8,9] and with brain atrophy in the temporal lobe [10,11]. Moreover, recent studies in presbycusis have shown cortical atrophy in regions beyond the auditory cortex, including the cingulate cortex and parietal regions [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…After the whole-brain analysis, we selected regions of interest that have been consistently implicated in previous neuroimaging studies relating audition, cognition, and dementia (Li et al, 2017;Ren et al, 2018;Xu X.-M. et al, 2019). To define ROI's, we used the Desikan-Killiany atlas, a gyrus-based atlas (Desikan et al, 2006) that has been commonly employed to explore cortical morphometry (Fornito et al, 2013;Jalbrzikowski et al, 2013).…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…In addition to the behavioral changes that precede dementia, recent studies suggest that biomarkers of neurodegeneration such as brain atrophy in certain areas could predict cognitive decline and dementia (ten Kate et al, 2018). Likewise, subjects with presbycusis have gray matter atrophy in the temporal lobe (Lin et al, 2014), as well as in nodes of the default mode network (Ren et al, 2018), such as the insula and the cingulate cortex. In this sense, we recently found that subjects with presbycusis and cochlear dysfunction, as evidenced by the loss of otoacoustic emissions, have atrophy of the cingulate and temporal cortices, which were related to executive dysfunction and depressive symptoms (Belkhiria et al, 2019).…”
mentioning
confidence: 99%
“…Also cross-sectional work has shown that pure-tone hearing loss is related to neuroanatomical alterations of gray matter volume and thickness (Alfandari et al, 2018;Eckert et al, 2012;Rigters et al, 2018Rigters et al, , 2017Tuwaig et al, 2017;Rudner et al, 2019;Uchida et al, 2018;Ren et al, 2018;Armstrong et al, 2019;Neuschwander et al, 2019;Giroud et al, in prep., but see Profant et al, 2014).…”
Section: Frontal Cortical Thickness As a Correlate For Successful Sinmentioning
confidence: 99%